LITERATURE REVIEW : TERAPI NON FARMAKOLOGI PADA KLIEN POST OPERASI HERNIOTOMI DENGAN NYERI AKUT - Condrosasi, Luh (Universitas Harapan Bangsa Purwokerto, 2020)
Background: Hernia is an emergency condition that requires immediate treatment by performing surgery in the form of a herniotomy surgery. An incision during a herniotomy can cause tissue damage, which can lead to postoperative pain or surgery. Purpose: The purpose of this review literature is to analyze what non-pharmacological therapies can be used to treat post herniotomy surgery pain. Method: This study explores quantitative evidence or the results of 11 scientific journals published in an electronic database in the form of Google Scholar by including three keywords in the form of